Effect of Acupressur and Oxytocin Massage on Output Time and Adequacy Of Breast Milk in Post Partum Mothers at Panembahan Senopati Hospital, Bantul - Rusmini .; Any Ashari; Yuni Kusmiyati (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Breastfeeding provides benefits for both mother and baby. Breasti imilk containsi imany nutrientsi ithat babiesi need ini ithe ifirst 6i (six) months after birth. There are factors that influence exclusive breastfeeding that can inhibit the secretion of the oxytocin hormone. One way to stimulate the oxytocin hormone and increase comfort is by oxytocin massage. The prolactin and oxytocin hormones play a very important role in the adequacy of breast milk production. One way to generate the let down reflex is by doing therapy acupressure. The purpose of this study was to analyze the effect of giving little finger acupressure and oxytocin massage to the output time and adequacy of breastfeeding in postpartum mothers at Panembahan Senopati Hospital, Bantul. The design of this research is the Randomized Controlled Trial (RCT) with a quantitative approach. The population in this study were all postpartum mothers who experienced vaginal delivery at the Panembahan Senopati Hospital Bantul in 2021, as many as 166 people. The number of samples in this study was 70 postpartum mothers who met the inclusion criteria based on the calculation of the slovin formula. The results showed that acupressure had more effect on the time of output and the adequacy of breast milk than oxytocin massage for postpartum mothers at RSUD Panembahan Senopati Bantul.